Employment security and health. Issue 8 (1st August 2002) - Virtanen, P; Vahtera, J; Kivimäki, M; Pentti, J; Ferrie, J
Abstract : Objective: To study the relation of contractual and perceived employment security to employee health. Design: Cross sectional survey. Setting: Municipal sector employees in eight Finnish towns. Participants: 5981 employees with a permanent contract and 2786 employees with a non-permanent contract (2194 fixed term contract, 682 government subsidised contract). Outcome measures: Poor self rated health, chronic disease, and psychological distress. Results: Compared with permanent employees, fixed term men and women had better self rated health (men odds ratio 0.70; 95% confidence intervals 0.50 to 0.98, women 0.70 (0.60 to 0.82) and less chronic disease (men 0.69; 0.52 to 0.91; women 0.89; 0.79 to 1.02), but women had more psychological distress (1.26; 1.09 to 1.45). The only difference between subsidised employees and permanent employees was the high level of psychological distress in women (1.35; 1.09 to 1.68). Low perceived employment security was associated with poor health across all three indicators. The association of low perceived security with psychological distress was significantly stronger in permanent employees than among fixed term and subsidised employees, indicating that perceived security is more important for mental health among employees with a permanent contract. Conclusions: Contractual security and perceived security of employment are differently associated with health. It is therefore important to distinguish between these aspects of employment security in studies of labour market status and health. Such studies will also need to control for health selection, which is unlikely to operate in the same way among permanent and non-permanent employees.